The utility of university-industry partnerships : a case study of the University of Cape Town (UCT) and SASOL - Cele, Mlungisi B. Gabriel; Mouton, Johann (Stellenbosch : University of Stellenbosch, 2010)
116 leaves single sided printed, preliminary pages i-viii and numbered pages 1-106. Includes bibliography.